The theory and practice of carrying out the marketing competition at the industrial enterprise of a chemical complex - A. A. Zhdanov (Путеводитель предпринимателя)
By author competition represents process is defined as profit increase targeted activity. In the case of distribution competition profit increased by distribution management. Suggested recommendations touch different subjects of distribution competition management: defining of competitive groups in company product range; supply channels development priorities; defining of supply alternatives; conducting ofanalysis related to competitiveness of company products compared to competitive products and substitutes; organizing of work dedicated to creature and development of production chains; business result estimation. Based on practical experience, author finds out features of distribution competition in chemical industry and develops practical recommendations. It is considered a case of project dedicated to creature and development of production chains in order to increase sales of fluoropolymers by chemical company HaloPolymer.